Eco-Theology in Practice through Religious Leadership and Water Conservation by Romo Kirjito in Central Java - Jakti, Najata Hammada; Hidayatullah, Ahmad Fauzan; Davany, Almira Belva; Kullu Jasad, Laila Lathifah (Jurnal Studi Agama dan Masyarakat, 2025)
The clean water crisis has become a pressing issue in highland areas such as Dusun Bunder, Klaten. Limited groundwater sources have encouraged the local community to independently develop rainwater conservation systems. This study aims to examine the practice of ecotheology embodied through the religious leadership of Romo Kirjito in water conservation, and to analyze its contribution to environmental sustainability and the strengthening of interfaith harmony. The research employed a qualitative method with a case study approach. Data were collected through field observations, in-depth interviews, and document analysis. The data were analyzed descriptively and qualitatively through stages of data reduction, categorization, and interpretation based on ecotheological theory. The results indicate that water conservation in Dusun Bunder is not only technical in nature, but also integrated with religious values and local traditions. Innovations such as rainwater harvesting and electrolysis technology were developed through participatory community efforts. This research complements studies on the relationship between environmental spirituality and community-based conservation practices. The findings suggest that local leadership and interfaith values can serve as a strong foundation for sustainable water management. This model can be replicated in other areas facing similar challenges.